Optimism in Using Platform Merdeka Mengajar to Support Primary School Teachers’ Practice - Krismiyati, Krismiyati; Latuperissa, Rudy (International Journal of Active Learning, 2024)
Platform Merdeka Mengajar (PMM) has been launched since 2020. Since then, it has become a resource for teachers to support their teaching and learning activities. The platform offered many opportunities for the teachers to build and develop their capacity for a better quality of teaching, from planning to classroom practices. It was essential to know their view of using the platform. This study aimed to investigate the teachers' optimism in using the platform. Besides, it explored what factors influenced their optimism in using  PMM. The study used a quantitative approach to see the teachers' general tendency regarding their optimism. It involved 303 primary school teachers as the participants. It used a 5-point Likert scale questionnaire for the data collection. The analysis data covered the reliability and validity of the items, descriptive analysis, and correlation between the items constructing the optimism. The study's findings showed that the teachers in this study had a high optimism of 4.17. The study also described that planning the lesson, flexibility, capacity building, and teachers’ productivity did affect their optimism in using Platform Merdeka Mengajar. Further research recommendations were described in the conclusion section.